Neuron tau-targeting biomimetic nanoparticles for curcumin delivery to delay progression of Alzheimer’s disease - Chunhong Gao; Xiaoyang Chu; Wei Gong; Jinpeng Zheng; Xiangyang Xie; Yuli Wang; Meiyan Yang; Zhiping Li; Chunsheng Gao; Yang Yang (Journal of Nanobiotechnology, 2020)
Abstract Background Although many therapeutic strategies for Alzheimer’s disease (AD) have been explored, these strategies are seldom used in the clinic. Therefore, AD therapeutic research is still urgently needed. One major challenge in the field of nanotherapeutics is to increase the selective delivery of drugs to a targeted location. Herein, we devised and tested a strategy for delivery of nanoparticles to neurons to inhibit tau aggregation by directly targeting p-tau. Results Curcumin (CUR) is loaded onto red blood cell (RBC) membrane-coated PLGA particles bearing T807 molecules attached to the RBC membrane surface (T807/RPCNP). With the advantage of the suitable physicochemical properties of the PLGA nanoparticles and the unique biological functions of the RBC membrane, the RPCNP are stabilized and promote sustained CUR release, which provided improved biocompatibility and resulted in long-term presence in the circulation. Under the synergistic effects of T807, T807/RPCNP can not only effectively penetrate the blood–brain barrier (BBB), but they also possess high binding affinity to hyperphosphorylated tau in nerve cells where they inhibit multiple key pathways in tau-associated AD pathogenesis. When CUR was encapsulated, our data also demonstrated that CUR-loaded T807/RPCNP NPs can relieve AD symptoms by reducing p-tau levels and suppressing neuronal-like cells death both in vitro and in vivo. The memory impairment observed in an AD mouse model is significantly improved following systemic administration of CUR-loaded T807/RPCNP NPs. Conclusion Intravenous neuronal tau-targeted T807-modified novel biomimetic nanosystems are a promising clinical candidate for the treatment of AD.